Bar-On, Legacy of Silence - Encounters with Children of the Third Reich. Kerschaw, The Nazi Dictatorship - Problems and Perspectives of Interpretations - Firsching, Lorenz (Teaching History: A Journal of Methods, 1991)
Dan Bar-On’s Legacy of Silence is a collection of interviews with children of the perpetrators of the Holocaust–the children of Nazi officials who participated in or witnessed the mass murders of the Jews. Dar-On, an Israeli psychologist whose family left Germany in 1933, offers a new, moving, and disturbing complement to the more usual studies of the victims of Nazi genocide and their children. Just as the children of Nazi victims carry a life-long legacy of their parents’ experiences, Bar-On suggests that the children of the Nazi perpetrators also bear a legacy of their parents’ deeds, a legacy of silence. Bar-On freely admits that his book is not an objective, "social science" approach to the effects of genocide. "When I return from my fourth trip to Germany in October 1987," he writes in his conclusion, "I feel a tremendous need to try to ’analyze my data’ ... But I know I am doing something wrong ... I am distancing myself from my interviewees, looking at them from the outside ... I wonder if this is a result of my ongoing ambivalence about the research: am I afraid that if I look too closely I will see ordinary human beings?"